PANGAN TAK TERKONSUMSI PADA RUMAH TANGGA DI KECAMATAN LAWANG KIDUL KABUPATEN MUARA ENIM - Wenny Widiastuti; Muhammad Yazid; rni Purbiyanti (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2018)
Reducing food waste is one of the efforts to realize national food security. Research on households food waste was executed in Lawang Kidul District Muara Enim in April 2016. The method used in this research was survey. The method used to select the area was cluster sampling. The purposes of this research were to describe the process of food waste and describe the handling of food waste. In this research, food waste referred to rice waste produced by household. The process of food waste on households started from food (rice) consumption was conducted by household members in the primary meal the day or night. Primary meal and also a kind of side dishes/vegetables was consumed proved affecting appetite so that tend the cause of food waste in household.. The manner of handling food waste among others were; (1) used as cattle feed; (2) discarded as rubbish and; (3) use as organic fertilizer.